2022
DOI: 10.1101/2022.04.16.22273937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global reports of takotsubo (stress) cardiomyopathy following COVID-19 vaccination: a systematic review and meta-analysis

Abstract: Background and aimsConcerns have been raised recently about takotsubo cardiomyopathy after receiving COVID-19 vaccines, particularly the messenger RNA (mRNA) vaccines. The goal of this study was to compile case reports in order to provide a comprehensive overview of takotsubo cardiomyopathy associated with COVID-19 vaccines.MethodsFrom inception until March 10, 2022, a systematic literature search was conducted in PubMed and Google Scholar. The study included individuals who developed cardiac takotsubo cardiom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The minor differences between the studies could be as a result of higher number of included cases in our study than the previously conducted one in 2020 12 . A preprint systematic review on eight case reports which aimed to evaluate the features of TTS following COVID‐19 vaccine administration showed that all cases had abnormal ECG and an elevated troponin test, while all of them had LVEFs of above 50% 87 . In a study on 1216 patients with COVID‐19 who underwent echocardiography, evidence in favor of TTS was the least frequent cardiac complications that only found in solely 2% of them 88 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The minor differences between the studies could be as a result of higher number of included cases in our study than the previously conducted one in 2020 12 . A preprint systematic review on eight case reports which aimed to evaluate the features of TTS following COVID‐19 vaccine administration showed that all cases had abnormal ECG and an elevated troponin test, while all of them had LVEFs of above 50% 87 . In a study on 1216 patients with COVID‐19 who underwent echocardiography, evidence in favor of TTS was the least frequent cardiac complications that only found in solely 2% of them 88 .…”
Section: Discussionmentioning
confidence: 73%
“… 12 A preprint systematic review on eight case reports which aimed to evaluate the features of TTS following COVID‐19 vaccine administration showed that all cases had abnormal ECG and an elevated troponin test, while all of them had LVEFs of above 50%. 87 In a study on 1216 patients with COVID‐19 who underwent echocardiography, evidence in favor of TTS was the least frequent cardiac complications that only found in solely 2% of them. 88 The typical features of TTS in echocardiography are basal hypercontractility and apical ballooning.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 124 , 125 Takotsubo cardiomyopathy (TTC) Chest pain, transitory left ventricular failure, electrocardiographic abnormalities, an increased troponin level, the lack of occlusive coronary artery disease Admission to the hospital and supportive care All patients recovered from their symptoms, patients can typically resume their regular daily activities 80 % of the patients received the mRNA COVID-19 vaccine, while 20 % received other types. 134 Myocardial infarction (MI) Chest pain/discomfort Admission to the hospital and management based on guidelines Some patients developed heart failure, some cardiogenic shock, some were intubated, and some had cardiovascular-related mortality No exact statistics were found vaccine-induced thrombotic thrombocytopenia (VITT)/ pulmonary embolism (PE) Breathlessness, Pain in the chest or stomach, swelling or coldness in a leg, severe or worsening headache or blurred vision after vaccination, persistent bleeding, reddish or purplish spots, or blood blisters under the skin Admission to the hospital, treatment with nonheparin anticoagulation, followed by a rapid increase in platelet count 102 , 106 Thrombocytopenia associated, pulmonary embolism and portal vein thrombosis is more frequently in women under 55 Most frequently reported after the use of the Vaxzevria (AstraZeneca) vaccine(106), next after the use of Janssen, and rarely by the use of mRNA vaccines …”
Section: Resultsmentioning
confidence: 99%
“…The present case describes a presentation of typical TTS and Graves’ disease after the first dose of mRNA-1273 SARS-CoV-2 vaccination in a postmenopausal woman. A systemic review has recruited 10 cases with TTS following COVID-19 vaccination between 1 January 2020 and 1 June 2022 [ 3 ]. In total, 10 out of 11 patients were female, and 7 of them were older than 60 years old.…”
Section: Discussionmentioning
confidence: 99%